Physalins (13,L4-Seco-16,24-Cyclosteroids) Produciton in Physalis Minima (LINN.) - Gansau, Jualang (2001)
Physalis minima produces physalins, and these ell-steroidal lactone compounds have great potentials in phannaceutical industry. However, no detail infonnation on the biosynthetic background of physalins in either intact plants or in cultured plant tissues. Therefore, this study was carried out to determine the physalins distribution in intact plants and in cultured plant tissues: callus, cell suspensions and hairy roots. Factors that control the growth and physalins production in plant tissue culture levels such as medium compositions, physical factors and precursors were also elucidated to improve the physalins productivity. The results showed that physalins accumulation in specific plant tissues of intact plants varied between 0.07 to 5.76 mg g-t DW. Physalin contents increased two folds as the plant matured. Physalin A accumulated mostly in young fruits (3.82 mg g⁻¹ DW), physalin B in young leaves (1.56-3.20 mg g⁻¹ DW) and flower buds (2.88-3.60 mg g⁻¹ DW), physalin D in flower buds (4.65-5.83 mg g⁻¹ DW), physalin F in older leaves (4.51-9.89 mg g⁻¹ DW), physalin J in immature and ripe fruit calyx (2.14-3.96 mg g⁻¹ DW), and physalin N in young and old leaves (2.68-4.48 mg g⁻¹ DW). In addition, the accumulation level of physalins in specific tissues was different among plants collected from different locations. In cultured plant tissues, the content of physalin B and F in hairy roots were found to be higher (1.95-17.01 mg g⁻¹ DW) than that in intact plants, but lower in callus (1.51-1.91 mg g⁻¹ DW) and cell suspension (0.67-1.95 mg g⁻¹ DW) cultures. Higher physalins production in callus and suspension cultures were obtained in cells derived from leaves followed by root and stem explants. Cell suspension and hairy root cultures were also capable of excreting physalins at lower concentration into culture medium. The study on the effect of medium compositions has shown that higher physalins production in callus. cell suspension and hairy root cultures were obtained in 1/2MS (half strength), MS (full strength) and B5 (full strength) basal media, each supplemented with 2.5, 3.5 and 3.5% (w/v) sucrose, respectively. An auxin-cytokinin interaction was observed to be important for callus cultures, as these two classes of phytohonnones afe required for higher growth and physalins production. Higher physalins production in callus culture was obtained in medium supplemented with a combination of 2,4-D and kinetin (9.0:4.5 1lM). However, the addition of cytokinin in cell suspension culture appeared to stimulate irregular compact globular cells and growth of many root-like structures in the cell clumps. Higher physalins production in cell suspension was obtained in cultures supplemented with 9.0-18.0 µM NAA or 18.0 µM lAA. Meanwhile, in hairy root cultures, phytohormones often caused a growth disorganisation. The addition of 3-4 J,J.M NAA increased the physalins production. Further investigations on hairy root cultures have shown that physaJins accumulated mainly in mature part of root tissues. Inoculum of different root morphology did not significantly influence growth and physalins production. Meanwhile, the increase in number of inoculum root tips and medium volume resulted in changes of certain growth parameters. Hairy root cultures were capable to grow in pH values between 4.0-9.0, and higher physalins production was obtained at pH 5.0-7.0. Physalin productions in hairy roots also increased up to 1. 2.1 folds when cultured under dark conditions supplemented with alanine, leucine and valine.